Limited evidence of moderation of the association between gastrointestinal symptoms and prospective healthcare utilisation by quality of life. Issue 3 (19th October 2021) - McNaughton, David T.; Andreasson, Anna; Ljótsson, Brjánn; Beath, Alissa P.; Hush, Julia M.; Ljunggren, Gunnar; Schmidt, Peter T.; Talley, Nicholas J.; Agréus, Lars; Jones, Michael P.
Summary: Background: An individual's drive to seek medical help remains a complex behavioural process, incorporating psychological, social and symptom‐specific factors. Within irritable bowel syndrome (IBS), gastrointestinal symptoms only predict a small portion of the high healthcare‐seeking experienced. Aim: To examine the moderating role of quality of life (QoL) domains on this relationship to help explain the variance observed. Methods: This is an analysis of a Swedish population‐based prospective study of healthcare use over a 12‐year period. At baseline, gastrointestinal symptoms were measured with the valid Gastrointestinal Symptom Rating Scale, and QoL via the SF‐36. 1159 subjects (57% female; mean age 48.6 years) had their health records matched with the initial survey. 164 were classified as IBS by Rome II criteria. Negative binomial or logistic models were fit to evaluate the moderating effect of particular QoL domains on the relationship between gastrointestinal symptoms and prospective healthcare utilisation. Results: Gastrointestinal symptoms were associated with prospective healthcare use, but moderation in this relationship by particular QoL domains was not supported; most models did not reach statistical significance. Furthermore, the impact of IBS status did not alter the moderation hypotheses. Conclusions: Particular QoL domains did not impact the relationship between gastrointestinal symptoms on prospective healthcare seeking. Future research should continue to examine other psychological, social and symptom variables to identify predictors of high healthcare consumers in IBS. Abstract : Positive association between GI symptoms and prospective healthcare utilization.Limited evidence of moderation by quality of life was identified.